Case Report: Robotic ALPPS Procedure for Hepatocellular Carcinoma in the Right Lobe of the Liver - Solomonov, Evgeny; Tzadok, Itamar; Stemmer, Salomon; Biswas, Seema (Frontiers in Surgery, 2021)
Introduction: Associating liver partition with portal vein ligation for staged hepatectomy (ALPPS) is a surgical procedure for liver malignancy where the volume of the liver remnant is estimated to be too small. We present the first case of two-stage robotic ALPPS procedure, illustrating the steps and advantages of robotic surgery. Materials and Methods: A 68-year-old man with morbid obesity (BMI 40), portal fibrosis, macrovesicular steatosis, and poor liver function underwent robotic ALPPS for hepatocellular carcinoma in the right lobe of the liver (segments 5, 7, and 8). A video presentation (https://youtu.be/M50Gumf-4pw) of the operative procedure is accompanied by explanation in the text with embedded corresponding video time points. Results: Both stages of the procedure were performed robotically, with negligible blood loss, and rapid surgical recovery. The patient died 3 years later. Discussion: Robotic ALPPS offers reduced morbidity in major liver surgery for malignancy and may extend survival in meticulously selected patients.